Instrumentation and Data Analysis Tools for Complex Metabolomics Using Multidimensional Chromatography and Mass Spectrometry - Morimoto, Joshua. (Tufts University. Tisch Library., 2021)
Thesis (Ph.D.)--Tufts University, 2021.; Submitted to the Dept. of Chemistry.; Advisor: Charles Mace.; Committee: Colin Orians, Samuel Thomas, and Dwight Stoll.; Keyword: Analytical chemistry.